Features of the Use of Renewable Energy Sources in Agriculture - Bolyssov, Tokhtar; Yessengeldin, Bauyrzhan; Akybayeva, Gulvira; Sultanova, Zamzagul; Zhanseitov, Azamat (International Journal of Energy Economics and Policy, 2019)
The article considers the prospects of using renewable energy sources in agriculture. The authors focused on the following types of renewable energy sources: Solar, biomass, wind, and hydro generated power. Based on the analysis of Renewables Global Status Report data, the authors identified a decrease in the amount of investment in renewable energy and fuel by developed countries in developing countries. This work highlights the main reasons for the development of renewable energy (environmental safety, energy independence), as well as positive and negative aspects of the transition to renewable energy. The authors of the article reveal the features of job creation in the renewable energy industries, which will compensate for the loss of jobs in the field of fossil energy. Much attention is paid to the economy of renewable energy sources, revealing the relationship between energy use and economic growth. According to the authors, the use of RES not only increase the level of energy supply to remote rural settlements, but also can have a significant positive impact on the economy of agriculture. Keywords: Agriculture, Renewable Energy Sources, Energy Economy JEL Classifications: Q10, Q29 DOI: https://doi.org/10.32479/ijeep.7443